Factors Associated With Early Functional Outcome After Hip Fracture Surgery. (March 2016) - Cohn, Matthew R.; Cong, Guang-Ting; Nwachukwu, Benedict U.; Patt, Minda L.; Desai, Pingal; Zambrana, Lester; Lane, Joseph M.
Background: Hip fractures are common in the elderly and are likely to become more prevalent as the US population ages. Early functional status is an indicator of longer term outcome, yet in-hospital predictors of functional recovery, particularly time of surgery and composition of support staff, after hip fracture surgery have not been well studied. Methods: Ninety-nine consecutive patients underwent hip fracture surgery by a single surgeon between 2009 and 2013. Surgery after 48 hours was deemed as surgical delay, and surgery after 5pm was deemed as after hours. Surgical support staff experience was determined by experts from our institution as well as documented level of training. Functional status was determined by independent ambulation on postoperative day (POD) 3. Results: On POD3, 48 (79%) of 62 patients with no delay were able to ambulate, whereas only 14 (38%) of 37 patients with delayed surgery were able to ambulate ( P < .001). This relationship persisted when adjusted for American Society of Anesthesiologist classification. No delay in patients older than 80 (odds ratio [OR], 6.91; 95% confidence interval [CI], 2.16-22.10) and females (OR, 7.05; 95% CI, 2.34-21.20) was associated with greater chance of early ambulation. After-hours surgery was not associated with ambulation ( P = .35). Anesthesiologist and circulating nurse experience had no impact on patient's ambulatory status; however, nonorthopedic scrub technicians were associated with worse functional status (OR 7.50; 95% CI, 1.46-38.44, P = .01). Conclusion: Surgical delay and nonorthopedic scrub technicians are associated with worse early functional outcome after hip fracture surgery. Surgical delay should be avoided in older patients and women. More work should be done to understand the impact of surgical team composition on outcome.